Writing an article for a refereed accounting journal. Issue 3 (4th November 2014) - de Villiers, Charl; Dumay, John
Abstract : Purpose: – This article aims to focus on areas that can potentially improve a manuscript's chances of success, i.e. acceptance for publication. In particular, we deal with topic selection, as well as aspects that can improve the manuscript during the writing phase, including the style of prose and citations. Design/methodology/approach: – Recommendations are based on a review of the literature and our own experience. To demonstrate the practical application of the issues that need to be dealt with, examples have been provided from research articles published during 2010 in Accounting, Organizations and Society ( AOS ) and Accounting, Auditing & Accountability Journal ( AAAJ ). Findings: – There are some common reasons for rejection that can be avoided, but one of the most important issues is to ensure that the research question is novel and that this novelty is made explicit in the introduction to the manuscript. The novelty–rigour curve (or NR curve) is introduced and the relationship between novelty and rigour, as it relates to a manuscript's likelihood of acceptance for publication, is explained. The assessment of the prose used in published articles reveals that there are no set rules. Research limitations/implications: – This article does not reveal guaranteed recipes for success, except that careful consideration and motivation of the novelty and rigour of the research undertaken are important. The authors suggest research into reviewer behavioural aspects as a possible avenue for future research. Originality/value: – The novelty-rigour curve that depicts and explains the requirements of, and relationship between, these two research attributes is introduced. This article is novel because the prose of research articles published in AOS and AAAJ is critically examine in an attempt to assist both early career researchers to break into the top tier of accounting journals and established academics to enhance their chances of success. As such, the article has practical value for accounting academics and may also stimulate discussion among reviewers, editorial board members and editors, thereby playing a role in developing the field of accounting academic publishing.